2017
DOI: 10.1093/cid/cix560
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium malariae in Israeli Travelers: A Nationwide Study

Abstract: The relative proportion of P. malariae is on the rise. Diagnosis in routine clinical settings is inadequate due to the low sensitivity and specificity of blood smears. PCR should be considered when clinical suspicion is high. Prophylaxis failure, which caused delayed clinical presentation, was documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Despite the high attack rate in the present report, there were no cases of anemia or nephritis, which are the most serious clinical manifestation of P. malariae [7][8][9]. Although it has been reported that P. malariae may be intrinsically less susceptible to artemisinin than P. falciparum [11,12], all patients in the current outbreak responded to treatment indicating that the strain was not resistant to the anti-malarials used.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Despite the high attack rate in the present report, there were no cases of anemia or nephritis, which are the most serious clinical manifestation of P. malariae [7][8][9]. Although it has been reported that P. malariae may be intrinsically less susceptible to artemisinin than P. falciparum [11,12], all patients in the current outbreak responded to treatment indicating that the strain was not resistant to the anti-malarials used.…”
Section: Discussioncontrasting
confidence: 67%
“…Plasmodium malariae infection is often asymptomatic, rarely leads to severe clinical illness or death, and is typically associated with a low-grade chronic infection that can persist for extended periods of time, perhaps even decades [7,8]. The disease has been linked to nephropathy and anemia [9,10]. Although the distribution of P. malariae is rather patchy, it has been observed in all major malaria-endemic regions of the world, throughout tropical Africa, Southeast Asia, and Central and South America [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cases of imported malaria have been reported among returning travelers. One study reported 18 cases of P. malariae infection among Israeli travelers who had visited Africa from January 2008 to January 2017 [60]. A more recent study carried out at Chaim Sheba Medical Center in Tel Aviv reported that 145 malaria cases were detected among 722 patients hospitalized during 2004 to 2015.…”
Section: Epidemiology Of Malaria In Israelmentioning
confidence: 99%
“…13 However, recent improvement in polymerase chain reaction (PCR) technique increased the identification of P. malariae that might have been misdiagnosed as fever of unknown origin. 35 Although there were reports of late onset and recrudescent fever despite adherent chemoprophylaxis, subsequent treatment has been paradoxically successful with the same medication. 3,5,6 Because of P. malariae ’s long senescent periods, recrudescent ability, and low parasite burden, clinicians must have high clinical suspicion and consider repeating LM when resource is limited or using PCR for diagnosis.…”
mentioning
confidence: 99%